(untitled) (Global Journals of Research in Engineering, 2013)
How does the Tunisian consumer react to drinking water quality This question is still unexplored because quality was always assumed to be homogeneous while it is not This paper provides answers and allows us to test the importance of the variable quality as a key determinant of global and regional drinking water demand function Greater Tunis Sousse and Gabes Design methodology approach We have used through an exploratory survey of a sample of 1200 households econometric estimates to determine the weight that Tunisian consumers ascribe to the variable quality in their water demand functions Results The estimated demand functions in the regions of Greater Tunis Sousse and Gabes revealed the importance of quality as a fundamental determinant of quantities requested by consumers The empirical analysis has shown that in Greater Tunis water quality is not a constraint on demand However in the regions of Sousse and Gabes water quality is an important factor in determining consumer behaviour Research limitations implications The empirical results depend on the 2004 survey